Influence of Pinus pinea plantation on physico-chemical and biological soil properties in Quercus ilex climax areas in Campania (Southern Italy) - Iovieno P.; Alfani A. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Pinus pinea plantation effects on soil physico-chemical and biological properties were investigated in two Mediterranean protected areas, where Quercus ilex woods represent the climax vegetation. Organic matter content, pH, electrical conductivity, N and S contents, available K, Mg, Mn, Cu and Fe contents, basal respiration, microbial biomass and Degens' Catabolic Response Profile were determined in Pinus pinea and Quercus ilex soils in both areas. Pinus pinea appear to affect most of the investigated soil properties; at both areas, Pinus pinea soils showed higher organic matter content and C/N ratio and lower pH than Quercus ilex soils: the availability of Mg and Fe were higher and Cu lower in pine soils. The availability of Mn and K as well as biological properties were also influenced by the tree cover but in different ways at Vesuvius and San Silvestro. Other environmental factors, such as soil mineralogic properties and seasonal effects were also important.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)